2018
DOI: 10.1111/jav.01455
|View full text |Cite
|
Sign up to set email alerts
|

Local use of landfills by a yellow‐legged gull population suggests distance‐dependent resource exploitation

Abstract: Understanding the use of feeding sources at the local scale is crucial in comprehending the factors driving population dynamics, dispersal and territory use. Many gull (Larus spp.) populations have increased sharply, which is partly promoted by their use of landfills as a food resource. Although at the large scale it is known that birds from mainland colonies feed more on landfills than those from offshore colonies, at the local scale, this distance‐dependent exploitation has been little studied. Here, then, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…), yellow‐legged gulls ( Larus michahellis , Egunez et al. ), and white storks ( Ciconia ciconia , Gilbert et al. ), is increasing in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), yellow‐legged gulls ( Larus michahellis , Egunez et al. ), and white storks ( Ciconia ciconia , Gilbert et al. ), is increasing in different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…After visual exploration of the trajectories, we divided the tracking data into yearly individual trajectories starting on 15 January, to minimize the probability of the starting point falling within a migration (following recommendations in Spitz et al 2017). We used the R packages adehabi-tatLT (Calenge 2006) and rpostgisLT (Dukai et al 2016) for data processing and exploration, respectively. We screened the resulting yearly individual trajectories to assess whether they included sufficient data for model fitting.…”
Section: Data Preparationmentioning
confidence: 99%
“…Studies based on ring‐recovery data, and more recently from satellite‐tracking devices, have demonstrated that distance to a particular food resource determines the extent to which it will be used by individuals from nearby gull colonies, even at relatively small scales (e.g. tens of kilometres; Egunez et al , ). In other words, even though gulls are efficient flyers and are able to cover long distances to find food (Isaksson et al , ; Kazama et al , ), there is evidence that the use of certain feeding sources can be very local.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of gulls take great profit from exploiting feeding sources of human origin all around the world, such as fish discards or refuse tips [1][2][3]. When such resources are abundant and predictable over time, they can have a very deep impact into population parameters like survival [4], breeding performance [5,6], or dispersal [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The Basque region in northern Iberia is closing all its open-air landfills [8], which hence provides a good chance to account for the effects of this process on the diet and territory use of the local yellow-legged gulls Larus michahellis. The population of this species within the region reached a size of up to ca.…”
Section: Introductionmentioning
confidence: 99%